“When a bad thing happens…you are better only when you are home:” alienation and mental health challenges experienced by Congolese and Somali migrants in Johannesburg, South Africa - Walker, Rebecca; Lakika, Dostin; Makandwa, Tackson; Boeyink, Clayton (Frontiers in Human Dynamics, 2023)
This article explores the link between migration and alienation and its impact on the mental health and wellbeing of Congolese and Somali asylum seekers and refugees—two of the largest populations of displaced migrants in South Africa. Drawing on ethnographic research in Johannesburg, we highlight the various ways alienation is both imposed upon and experienced by migrants and argue that systemic disintegration, or acts of alienation, can be seen as deliberate and active policies and practices that are instrumental in excluding asylum seekers and refugees from everyday life. The experiences of marginalization and othering narrated by Congolese and Somali migrants highlight ways in which alienation and disintegration from critical social connections including family, community, and familiar contexts fundamentally impact wellbeing and mental health as well as strategies of care-seeking, and other forms of relational resilience. While conceptualizations and metrics of integration may in some ways capture the fallout of disintegration, such as access to livelihoods, housing, education, and healthcare, we suggest that this does not adequately assess the profound damage by acts of alienation on crucial relationships. The alienated psyche of innumerable migrants in South Africa results in the feeling that “when a bad thing happens…you are better only when you are home.” This pain, or feelings of alienation, we argue, are a crucial aspect to our understanding of alienation and in turn, highlight the importance of alienation as an apt analytical tool through which experiences of asylum-seeking in South Africa can be understood.